Estimating the treatment cascade of chronic hepatitis B and C in Greece using a telephone survey. Issue 4 (11th September 2014) - Papatheodoridis, G.; Sypsa, V.; Kantzanou, M.; Nikolakopoulos, I.; Hatzakis, A.
Summary Accurate diagnosis and treatment rates for chronic hepatitis B (HBV) and C virus (HCV) infections are usually missing. Aim of this study was to estimate the HBV and HCV treatment cascade (proportion and absolute numbers of tested, aware/unaware, infected and treated) in Greek adults. A telephone survey was conducted in a sample representative of the Greek adult general population. Prevalence rates were age‐standardized for the Greek adult population and corrected for high‐risk individuals not included in the survey. Of the 9974 participants, 5255 (52.7%) had been tested for HBV and 2062 (20.7%) for HCV with the proportion varying according to age and being higher in middle‐age groups (P < 0.001). HBsAg was reported positive in 111/5255 (2.11%) and anti‐HCV in 26/2062 (1.26%) tested cases. The age‐adjusted prevalence was estimated to be 2.39% for HBV and 1.79% for HCV. Taking into account individuals at high risk for viral hepatitis not included in the survey, the 'true' prevalence was estimated to be 2.58% for HBV and 1.87% for HCV. Anti‐HBV and anti‐HCV treatment had been taken by 36/111 (32.4%) chronic HBV and 15/26 (57.7%) chronic HCV patients. In conclusion, almost 50% of chronic HBV and 80% of chronic HCV patients in Greece may be unaware of their infection, while only 32% or 58% of diagnosed chronic HBV or HCV patients, respectively, have been ever treated. Therefore, intensive efforts are required to improve the efficacy of screening for HBV and particularly for HCV as well as to reduce the barriers to treatment among diagnosed patients.